Home Energy Management System Concepts, Configurations, and Technologies for the Smart Grid - Usman Zafar (16875939) (2020)
Home energy management systems (HEMSs) help manage electricity demand to optimize energy consumption and distributed renewable energy generation without compromising consumers' comfort. HEMSs operate according to multiple criteria, including energy cost, weather conditions, load profiles, and consumer comfort. They play an increasingly ubiquitous role in energy efficiency through the reduction of electricity consumption within residential and commercial smart grids. This paper presents a comprehensive review of the HEMS literature with reference to main concepts, configurations, and enabling technologies. In doing so, it also provides a summary of HEMS computing trends and popular communication technologies for demand response applications. The ensuing survey offers the reader with an overall overview of current and future trends in HEMS solutions and technologies. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2020.3005244